Pendugaan Kebutuhan Air Tanaman Nanas (Ananas Comosus l. Merr) Menggunakan Model Cropwat - Tusi, Ahmad; Rosadi, Bustomi; Triana, Maruli (Balai Teknik Irigasi, 2012)
Pineapple is one of the potential plantation industries in Lampung Province. There are problems faced off in pineapple irrigation such as when and how much water must be applied to meet acceptable productivity and quality. The objective of this research was to know the water requirements by investigating and evaluating measurement methods of evapotranspiration using CROPWAT model. This research was conducted on Pineapple Farm in Terbanggi Besar, Lampung Tengah from October 2006 to January 2007. Three measurement methods of evapotranspiration applied were CROPWAT Model, based on Pineapple Farm calculation (control) and Pan evaporation Method were conducted and arranged in Randomized Completely Block (RCB) design with six replications. The results showed that the daily water requirements on October until December with 10-days irrigation frequency for CROPWAT Model were 1.25, 1.16, and 1.07 mm/day respectively; with the Control Method were 1.20 mm/day; and with Pan evaporation method were 1.13, 1.02, and 0.9 mm/day. Water requirements for plant was enough without suffering water stress. The comparison results showed that the evapotranspiration derived from CROPWAT Model data are generally 4.3% lower than Control data but by the Pan Evaporation were generally 16.4% lower than Control data. So, it confirmed that The average trend of plant growth indicators from CROPWAT Model having a reasonable good results for irrigation scheduling.